FIXED POINTS IN INTUITIONISTIC MENGER SPACE - Jain, Arihant; Gupta, V.K.; Bhinde, Ramesh (Italian Journal of Pure and Applied Mathematics, 2015)
The purpose of this paper is to use the new concept of absorbing mappings in intuitionistic Menger space and prove fixed point theorems, without appeal to continuity. The results thus obtained, generalizes and extends the result of Rashwan and Hedar [5] in intuitionistic Menger space. We also cited an example in support of our result.